Ogłoszenie prasowe źródłem wiedzy o kondycji etycznej człowieka. Wyimek z bibliografii tematycznej "Gazety Warszawskiej" R. 1789 = Press release is a source of knowledge about the ethical condition of man. The essay from the thematic bibliography "Gazeta Warszawska" R. 1789 - Grabias-Banaszewska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article puts the thesis that "Gazeta Warszawska" is a perfect material for the study of ethical attitudes of 18th-century society. The text is based on a thematic bibliography. The reflections are centered around the column "Reports from Warsaw" containing announcements concerning the search for missing persons, things and animals.
Keywords: historia prasy; ogłoszenia prasowe; Warszawa - 18 w.; monopol prasowy; press story; newspaper advertisement; Press Monopoly; Warsaw - 18th.